Principal Uses of Remote Sensing in Sea Ice Field Research - Robert Massom (2009)
As much as one-tenth of the world’s oceans are covered with sea ice, or frozen ocean water, at some point during the annual cycle. Sea ice thus plays an important, often defining, role in the natural environment and the global climate system. This book is a global look at the changes in sea ice and the tools and techniques used to measure and record those changes. The first comprehensive research done on sea-ice field techniques, this volume will be indispensable for the study of northern sea ice and a must-have for scientists in the field of climate change research.